MANAJEMEN LABA: BAGAIMANA DAMPAKNYA TERHADAP IPO UNDERPRICING? - Andre Yulius Sahat Nauli Sitompul; Unggul Purwohedi; Ari Warokka (Jurnal Keuangan dan Perbankan, 2017)
The purpose of this research was to investigate the effect of accrual and real earning management on IPO underpricing which was measured by initial return, on the first day of trading in Indonesia Stock Exchange, of Indonesian manufacturing companies during 2010-2014. This research was conducted using a purposive sampling technique from 20 analyzed manufacturing companies. Earnings management variable was measured using discretionary accruals, abnormal cash flow, abnormal production cost, and abnormal discretionary expenses while IPO underpricing was calculated using the initial return on the first day of stock trading in the stock exchange. This research used ordinary least squares technique (OLS) multiple linear regression analysis. The result of this study revealed that the real earning management practice through abnormal cash flow had a positive effect on IPO underpricing while the other earnings management proxy had a negative significant effect on underpricing. This finding indicated that every earnings management practice could give an effect in a different direction on IPO underpricing phenomenon, as a response of investors on the published company’s performance. Hence, this study’s finding provided a significant empirical contribution to the signaling theory, in particular for the issue of IPO underpricing in Indonesian Capital Market practices.